2002
DOI: 10.1007/s00056-002-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Torque Capacity of Metal and Plastic Brackets with Reference to Materials, Application, Technology and Biomechanics

Abstract: On the basis of the present results, the Brillant and Aesthetik-Line plastic brackets and the MINI-MONO metal bracket can be recommended for torquing. In view of the high torque losses, however, the torques programmed in the straight wire technique must be seen as questionable. It would be helpful to the practitioner if data were provided by the manufacturer on the flexing to be expected in plastic brackets, which has to be offset by additional torque or the possible renunciation of bracket torque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
3
28
2
3
Order By: Relevance
“…Our having observed significantly higher torque values associated with plastic brackets with a metal slot, as well as significantly lower torque values of all plastic brackets compared to metal brackets, concurs with the results of earlier studies [4,13,15,16,26].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our having observed significantly higher torque values associated with plastic brackets with a metal slot, as well as significantly lower torque values of all plastic brackets compared to metal brackets, concurs with the results of earlier studies [4,13,15,16,26].…”
Section: Discussionsupporting
confidence: 82%
“…Die Anwendung dieser neuen Produkte setzt die genaue Kenntnis der Materialeigenschaften voraus. Untersuchungen hier über liegen bis heute nur in geringer Zahl vor [1,4,8,13,15,16,26]. Reine Polycarbonatbrackets wiesen in früheren Untersuchungen eine mangelhafte Torquebelastbarkeit und Bruchfestigkeit auf [1,4,13,26].…”
Section: Introductionunclassified
“…Theoretically, the torque play could be estimated, using appropriate tables or formulas, at about 7-8u in the 0.022-inch slot and half that amount for a 0.017 3 0.025-inch in the 0.018-inch slot. 1,29,30 However, various experimental configurations revealed that torque play is actually higher in conventional 5,6,31 and self-ligating bracket systems.…”
Section: Discussionmentioning
confidence: 99%
“…4 Thereafter, considerable research has been conducted evaluating the torquing efficiency of various archwires into conventional and self-ligating brackets. [5][6][7][8][9][10][11][12][13] Direct comparison of these results is difficult because of differences in configurations and testing devices. Moreover, bracket positioning and small variations in curvature of the crowns or thickness of the adhesive could affect the generated moments and thus the final buccolingual tooth inclination.…”
mentioning
confidence: 99%
“…It has been found that forces as low as 0.2 N have generated tooth movement [12], and moments in the range of 5-20 Nmm cause tooth rotation [13]. Although it is Fig.…”
Section: Methodsmentioning
confidence: 99%